Analysis on anti-ice properties of aero aluminum alloy with weak wettability. (February 2019) - Qiu, C; Cheng, H; Chen, C; Li, M
Abstract: Aero aluminum alloy skin of airframe and aerofoil is easy to freeze at low temperature, and endangering flight safety. Therefore, it is of great importance to improve the anti-ice ability of aero aluminum alloy. In this paper, the contact characteristics of a single water droplet with aero aluminum alloy with different wettability is analyzed as well as the freeze of aluminum alloy at low temperature, and study the anti-ice properties of aero aluminum alloy with different wettability. The results indicate that the anti-ice capability of aero aluminum alloy is gradually enhanced with the weakening of surface wettability. And also the ice area is reduced, and the ice distribution is changed from facet to point gradually. When aero aluminum alloy becoming super hydrophobic surface, there are only few micro ice grains on the edge of surface.